Comparison between Rivet and Adhesive joints in Center Wingbox using Finite Element Method - ARYADHIA PRATAMA (NIM : 13113019), MUHAMMAD
Composite materials are used extensively as aircraft structures due to their design flexibility to create a light weight, high stiffness, and high ultimate stress structure. These structures are usually joined by using rivet joint because its simplicity and easiness for dissasembly. However, a study by Changing Wang found that machining process can cause rashes due to delamination in the composite. Adhesive joint technology can substitute the rivet joint in order to avoid the machining process. However, the technology still has high uncertainty due to its various failure mode which requires further research before it can substitute the rivet joint directly. The utilization of finite element analysis software such as ANSYS open the way to infinite development to adhesive bonding research by providing numerical solution to a real life case study that later turned into complex three dimentional model. It also allows many different designs to be simulated in order to perform a selection of different designs prior testing, which would consume a lot of time to be performed or be prohibitively expensive in practice. The purpose of this recent work is to observe the interaction between composite skin and framework made from aluminum alloy for two different sets of joint, one with mechanical fastener and the other with adhesive bonding using three dimentional real airplane wing structure. Two set of simplified aircraft center wingbox structure are made then given two different loading case which is pressure loading that are distributed along lower skin surface due to air lift on wing and the other loading case is bending moment towards upper direction due to the finite element model interaction with other set of frames that compose whole wing structure. A numerical study using ANSYS 16.2 was carried out to investigate the von Mises stress, maximum principal stress and maximum shear stress distribution characteristics which leads to identify the ultimate strength of adhesive bonded joint and how it compare to the conventional mechanical joint such as rivets under the same loading condition, due to air pressure and due to bending force.